Kualitas Fisik, Kandungan Protein Kasar dan Serat Kasar Jerami Padi yang Difermentasi dengan Cairan Rumen - Nursyam Andi Syarifuddin; Mailisa Sarfina (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2014)
Rice straws are classified as a low-nutritional quality of feed ingredients. Fermentationis an effort to improve the nutritional quality of rice straw as a feed for ruminant. Thepurpose of this study was to determine the optimal dose of ruminal fluid on physicalquality, crude protein content and crude fiber content of fermented rice straw. Theresearch design in this study was the Completely Randomized Design (RAL), with fivetreatments and four replications. The treatment was J1 (5% ruminal fluid), J2 (10%ruminal fluid), J3 (15% ruminal fluid), J4 (20% ruminal fluid) and J5 (25% ruminal fluid).The research was conducted at the Laboratory of Animal Production, Faculty ofAgriculture, Universitas Lambung Mangkurat, Banjarbaru, from February to April 2012.Results showed the addition of ruminal fluid on the rice straw very significantly affected(P>0.01) crude protein of fermented rice straw. However, addition ruminal fluid did notsignificantly affect (P<0.05) on temperature, moisture content, pH, and crude fibercontent of rice straw. Treatment J3 was the optimum rumen fluid dose as indicated byphysical quality of fermented rice straw, the highest content of crude protein (6.58%),and the lowest content of crude fiber (30,64%).